Peningkatan Kapabilitas Guru dalam Penggunaan Artificial Intelligence di MI Ar Raudhah Lawang: Studi Pelaksanaan Pelatihan dan Evaluasi Hasil Pelatihan - Henry Praherdhiono; Yulias Prihatmoko; Muhibuddin Fadhli; Nunung Nindigraha; Widi Hasanah; Kevin Herdinata cahyadi Firdaus (Universitas Negeri Malang, 2025)
In the era of the industrial revolution 4.0 and society 5.0, the ability to utilize technology, especially artificial intelligence, is crucial in various sectors, including education. AI has been proven to increase effectiveness and efficiency in the learning process, for example through assessment automation, personalization of learning materials, and analysis of student progress. For teachers, the ability to use and optimize AI is a powerful tool in supporting learning that is more adaptive, interactive, and centered on individual student needs. Improving the capabilities of teachers at MI Ar Raudhah Lawang in using AI aims to help teachers optimize learning and combine IMTAQ and IPTEK values. Improving teacher capabilities in using AI is in line with the goals of national education to form a generation that is intelligent, has character, and is competent in their fields. Teacher training related to the use of AI technology in learning is an ongoing process, which requires ongoing efforts and commitment. The training process is carried out in several steps: Providing an understanding of AI technology in learning, identifying training needs, making a training plan, providing practical training, providing support after training, and Evaluating training. The results of the training that has been carried out show an increase in the ability to utilize AI. Evaluation is carried out through pretests and post-tests to assess changes in teacher capabilities. Data from 15 respondents showed significant improvements in most aspects of the evaluation.